2017
DOI: 10.1016/j.ejvs.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Diverticular Disease and Abdominal Aortic Aneurysms: Pooled Analysis of Two Population Based Screening Cohorts

Abstract: An association was found between diverticular disease and AAA in a large population based cohort. Biological causality remains to be established, and a potential impact of diverticular disease on the natural history of AAA needs to be explored further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Colonic diverticulum and abdominal aortic aneurysms are initially asymptomatic, and both are frequently seen in the 5th and 6th decades. The relationship between aortic aneurysm and diverticulum has been shown in the literature 8 . However, no study reported comorbidity of abdominal aortic aneurysm and colonic diverticulum was found in the literature.…”
Section: Original Articlementioning
confidence: 99%
“…Colonic diverticulum and abdominal aortic aneurysms are initially asymptomatic, and both are frequently seen in the 5th and 6th decades. The relationship between aortic aneurysm and diverticulum has been shown in the literature 8 . However, no study reported comorbidity of abdominal aortic aneurysm and colonic diverticulum was found in the literature.…”
Section: Original Articlementioning
confidence: 99%